2022
DOI: 10.1155/2022/1924138
|View full text |Cite|
|
Sign up to set email alerts
|

Visual Resolve of Modern Educational Technology Based on Artificial Intelligence under the Digital Background

Abstract: With the development of Internet technology and the arrival of the knowledge-driven era, the breadth and depth of educational informatization are increasing day by day. Educational technology is not only a subject but also a career adapted to education and teaching. The growth speed of modern educational technology and the size of its benefits determine its management level to a large extent. With new technologies, new ideas, and new social needs, it is difficult for new ideas, new thoughts, and new methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Esos retos mencionados siguen latentes, sobre todo, porque la enseñanza a distancia ha tenido un aumento de demanda, no sólo por el Covid-19, sino también por el aceleramiento de las bondades de la tecnología y, por lo tanto, requiere una gestión de la información en una plataforma de la EaD que se adapte a características organizacionales como: apertura, dinamismo, flexibilidad, individualización y descentralización (Hong y Wang, 2022).…”
Section: Metodología Justificaciónunclassified
See 2 more Smart Citations
“…Esos retos mencionados siguen latentes, sobre todo, porque la enseñanza a distancia ha tenido un aumento de demanda, no sólo por el Covid-19, sino también por el aceleramiento de las bondades de la tecnología y, por lo tanto, requiere una gestión de la información en una plataforma de la EaD que se adapte a características organizacionales como: apertura, dinamismo, flexibilidad, individualización y descentralización (Hong y Wang, 2022).…”
Section: Metodología Justificaciónunclassified
“…También surge la necesidad de aplicar la IA a las tecnologías de educación actuales para mejorar la visualización 3 y digitalización 4 , necesarias para realizar investigación y adaptar los recursos educacionales en línea. Por otra parte, existen varios términos para la nueva tecnología educativa moderna (Hong y Wang, 2022) que contempla el uso de la actual, con los principios educativos de TI para imaginar, desarrollar, utilizar, tramitar y valorar los recursos de enseñanza y aprendizaje para la optimización educativa: la Educación a Distancia, entendida como la organización del proceso formativo, no limitado a un territorio de una institución educativa y que conlleva el uso de las últimas tecnologías (Pakhomova, et al, 2022).…”
Section: Metodología Justificaciónunclassified
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%